Analisa Hukum Terhadap Sistem Teknologi Global Positioning System (GPS) dalam Hak Atas Tanah - Maulidun Imam Akbar; Muhjad, Hadin; Ayu, Riana Kesuma (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2024)
Regulations regarding the GPS technology system in measuring and mapping land as a result of factual verification can cause corrections to the physical data and legal data in the certificate. Regarding this incident, if legal protection is based, the guideline is the certificate. The certificate as a BPN product refers to Article 19 UUPA jo. Article 32 paragraph (2) of the PP on Land Registration is valid evidence, except through cancellation by the BPN or annulment of the PTUN decision. In this case, the principle of Lex Superior Derogat Legi Inferiori applies, namely that higher regulations override lower regulations. If based on legal certainty, the results of factual mapping with GPS are the most valid physical and juridical land data and can be legally accounted for. The validity of the physical data and juridical data from this factual verification can be used as a basis for determination by BPN. This means that the principle of Lex Specialis Derogat Legi Generali applies, namely specific regulations override general regulations.